Discriminable Height Differences of Raised Lines. (May 2020) - Toyoda, Wataru; Miyamoto, Ryo; Oouchi, Susumu; Inoue, Takenobu
Introduction: The purpose of this study was to determine the discriminable height differences of raised lines printed on paper, as assessed by people who are blind, with or without years of tactile experience. Methods: Ten younger and 10 older tactile readers with blindness and with rich tactile experience; and 10 blindfolded, older, sighted participants with little tactile experience discriminated paired raised-line stimuli of different heights using the fingers of their preferred hand by active touch in a psychophysical experiment. Results: There was a significant main effect of the height of the stimulus, F (2, 54) = 56.446, MS = .060, p < .001, η p 2 = .676, η G 2 = .341, and participant group, F (2, 27) = 13.717, MS = .064, p < .001, η p 2 = .504, η G 2 = .357; however, there was no significant main effect of the width of the lines, or any interactions. The younger and older tactile readers had virtually similar thresholds and Weber fractions, and they could discriminate paired stimuli more accurately and efficiently than the older, sighted participants. We provided the discriminable height data of the raised lines based on the mean and 95th percentile values of the Weber fractions. Discussion: The results indicate the importance of tactile experiences for height discrimination in active touch. For older persons with recently developed blindness, raised lines with larger height differences should be used. Information for practitioners: These data will be helpful for developing new braille embossers that can print raised-line graphics for people with visual impairments, with or without years of tactile experience.